Analysis of spread of Phytophthora foot rot disease of black pepper by STCLASS - Software - Y. R. SARMA, M. ANANDARAJ and (Indian Phytopathology, 2002)
Phytophthora foot rot of black pepper (Piper nigrum), caused by P. capsici, is severe during the wet monsoon season. Observations on foot rot disease incidence were recorded on 6-year-old black pepper (cv. Karimunda) vines planted at Peruvannamuzhi.The pattern of spread was studied and analysed using STCLASS computer software. The pattern of spread was non-random and the initially infected vines served as source and focus of secondary spread.